Combining the Quick Wins approach with the PDCA Cycle for quick optimizations in a graphics industrial company - Silva, Ducely Lima; Santos, João Evangelista Dantas dos; Oliveira, Teresa Rachel Costa de; Figueiredo, Francisca Jeanne Sidrim de (Brazilian Journal of Production Engineering, 2025)
The study explored the integration of Lean, Quick Wins and PDCA methodologies in the printing industry, focusing on improving operational efficiency in a manual die-cutting sector. The problem addressed the need to optimize processes in a competitive, changing market, with reduced print runs and increasing digitalization. The objectives included the analysis of historical data, implementation of rapid improvements and validation of the PDCA cycle. The methodology involved a case study with quantitative and qualitative data analysis, using tools such as 5S and SMED to identify and mitigate inefficiencies. Quick Wins enabled immediate gains, while PDCA offered a cyclical structure for continuous improvement. The results showed a significant reduction in setup time, from more than 8 minutes to less than 3 minutes, in addition to improvements in organization and reduced movement. The implementation of 5S and reorganization of the layout contributed to a more efficient work environment. In conclusion, the integration of these methodologies proved to be effective in optimizing processes, increasing efficiency and employee satisfaction. The systematic approach of PDCA, combined with the agility of Quick Wins, has delivered tangible improvements, highlighting the importance of continuous adaptation in an ever-evolving industry.
Keywords: Quick Wins; PDCA Cicle; Quality Management; Graphic Sector